2022
DOI: 10.3390/toxins14030223
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hemocoagulase on the Prevention of Bleeding after Percutaneous Renal Biopsy

Abstract: A percutaneous renal biopsy is an essential tool for the diagnosis of various renal diseases; however, post-biopsy bleeding is a major complication. Hemocoagulase is a detoxified and purified snake venom enzyme that is widely used to prevent post-procedural bleeding. In this study, we retrospectively analyzed the effect of hemocoagulase on post-renal biopsy bleeding. We included 221 patients who underwent percutaneous renal biopsy between April 2017 and December 2020 and analyzed post-renal biopsy hemoglobin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Previous studies [19,20] have demonstrated that the application of hemocoagulase during hepatobiliary surgery can effectively reduce intraoperative bleeding volume without affecting the coagulation functions of patients. Furthermore, other studies [21,22] have shown that injection of hemocoagulase into rabbits accelerated blood coagulation without affecting platelet concentration. A study by Nascimento da Costa et al [23] found that hemocoagulase therapy does not confer the risk of deep vein thrombosis in the lower limb and is clinically safe and highly reliable in elderly patients.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies [19,20] have demonstrated that the application of hemocoagulase during hepatobiliary surgery can effectively reduce intraoperative bleeding volume without affecting the coagulation functions of patients. Furthermore, other studies [21,22] have shown that injection of hemocoagulase into rabbits accelerated blood coagulation without affecting platelet concentration. A study by Nascimento da Costa et al [23] found that hemocoagulase therapy does not confer the risk of deep vein thrombosis in the lower limb and is clinically safe and highly reliable in elderly patients.…”
Section: Discussionmentioning
confidence: 97%
“…A nephrologist performed kidney biopsies using a 16 G needle under ultrasonic guidance. Details of the procedure used in our hospital have been previously described [ 9 , 10 ]. The core samples were divided for assessment using light microscopy (LM), immunofluorescence microscopy (IF), and electron microscopy (EM).…”
Section: Methodsmentioning
confidence: 99%
“…Hemocoagulase, also known as batroxobin or reptilase, is a widely utilized clinical hemostasis agent for surgical hemostasis [ 135‐138 ] and bleeding prevention. [ 139‐140 ] It promotes platelet aggregation at the site of vascular damage, hydrolyzes the αA chain of fibrinogen, and converts fibrinogen into fibrin, thereby facilitating hemostasis. [ 141‐142 ] Kumar et al .…”
Section: Design Of Bioactive Hydrogel For Hemostasismentioning
confidence: 99%